Sinonim dalam Berita Agama pada Media Online BBC Arabic - Musyarrof, Muhammad 'Azmi; Safitri, Dewi Nur; Alifah, Heny Nur; Kamil, Ahmad Zulfa (Universitas Islam Negeri Walisongo Semarang - Indonesia, 2023)
This research aims to identify and collect synonyms in religious news about Hajj published in BBC Arabic online media. The method used is a descriptive qualitative, focusing on lexical cohesion analysis involving synonyms. The primary purpose of this research is to understand the variation of synonym usage in the context of religious news about Hajj and to classify the types of synonyms found. Data for this research was collected through documentation, using sources from news published by BBC Arabic. The research results indicate that 14 synonyms were found in the news. These synonyms can be classified into several types, including similar synonyms (Shibhu al-tarāduf), semantic relationship types (Al-taqārub al-dalālī), implication types (Istilzām), paraphrase types), and interpretation. This analysis provides a deeper understanding of the use of synonyms in the context of religious news about Hajj. It shows the richness of the Arabic language in conveying information on the topic. This research has important implications in linguistics, especially in understanding how synonyms are used in specific religious news contexts. This research also significantly contributes to the development of text analysis methodology and Arabic language research in general libraries.